Enantioselective pharmacokinetics of tramadol and its three main metabolites; impact of CYP2D6, CYP2B6, and CYP3A4 genotype. Issue 4 (5th July 2018) - Haage, Pernilla; Kronstrand, Robert; Josefsson, Martin; Calistri, Simona; van Schaik, Ron H. N.; Green, Henrik; Kugelberg, Fredrik C.
Abstract: Tramadol is a complex drug, being metabolized by polymorphic enzymes and administered as a racemate with the (+)‐ and (−)‐enantiomers of the parent compound and metabolites showing different pharmacological effects. The study aimed to simultaneously determine the enantiomer concentrations of tramadol, O ‐desmethyltramadol, N ‐desmethyltramadol, and N, O ‐didesmethyltramadol following a single dose, and elucidate if enantioselective pharmacokinetics is associated with the time following drug intake and if interindividual differences may be genetically explained. Nineteen healthy volunteers were orally administered either 50 or 100 mg tramadol, whereupon blood samples were drawn at 17 occasions. Enantiomer concentrations in whole blood were measured by LC‐MS/MS and the CYP2D6, CYP2B6 and CYP3A4 genotype were determined, using the xTAG CYP2D6 Kit, pyrosequencing and real‐time PCR, respectively. A positive correlation between the (+)/(−)‐enantiomer ratio and time following drug administration was shown for all four enantiomer pairs. The largest increase in enantiomer ratio was observed for N ‐desmethyltramadol in CYP2D6 extensive and intermediate metabolizers, rising from about two to almost seven during 24 hours following drug intake. CYP2D6 poor metabolizers showed metabolic profiles markedly different from the ones of intermediate and extensive metabolizers, with large area under the concentration curves (AUCs) of the N ‐desmethyltramadol enantiomers and low corresponding values of the O ‐desmethyltramadol and N, O ‐didesmethyltramadol enantiomers, especially of the (+)‐enantiomers. Homozygosity of CYP2B6 *5 and *6 indicated a reduced enzyme function, although further studies are required to confirm it. In conclusion, the increase in enantiomer ratios over time might possibly be used to distinguish a recent tramadol intake from a past one. It also implies that, even though (+)‐ O ‐desmethyltramadol is regarded the enantiomer most potent in causing adverse effects, one should not investigate the (+)/(−)‐enantiomer ratio of O ‐desmethyltramadol in relation to side effects without consideration for the time that has passed since drug intake.